Scalable high-efficiency metasurface-refractive retro-reflector - Quan Yuan; Qin Ge; Xiujuan Zou; Yi Zhang; Yuhang Yang; Boyan Fu; Ruoyu Lin; Boping He; Shuming Wang; Din Ping Tsai; Shining Zhu; Zhenlin Wang (PhotoniX)
Abstract A retroreflector, an optical device that reflects light back along its incident path, plays a crucial role in optics. However, achieving high-efficiency, large-area retroreflection in planar optical systems remains a persistent challenge, constrained by the bulky nature of traditional designs like corner cube mirrors and cat’s eye retroreflectors. Here, we demonstrate a scalable metasurface-refractive retroreflector (MRR) that combines a refractive lens and meta-lens, achieving polarization-independent retroreflection with a half power field of view (FOV) of 70° and 88.5% efficiency at normal incident. The scalability of the MRR enables straightforward planar expansion into arrays, facilitating large-area effective retroreflection. Additionally, a moving object equipped with MRR is observed in a laser tracking experiment. The metasurface-refractive architecture evidently improves the functionality of the retroreflector, and paves a new path in the field of smart optical device design.